2017
DOI: 10.5812/jamm.57335
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Determinants of Consistent Condom Use Among Cameroonian Soldiers

Abstract: Background: Despite numerous health promotion interventions lately conducted, the human immunodeficiency virus (HIV) remains a major cause of morbidity and mortality in sub-Saharan Africa. It is reported that military personnel have a higher prevalence of HIV, compared with the general population. Condom use remains a cheap, easy-to-use, and effective device to prevent the spread of HIV. Growing evidence, however, suggests its underuse among the military personnel. Methods: The current cross sectional study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…23,24 Regardless of the different strategies that promote condoms developed in this country, consistent condom use is still low in the police force. 25 The probable reason for this could be the information provided is not comprehensive enough and has not been tailored to this population as this is explained by this study. The main reasons for not using condoms consistently were reduced sexual pleasure 134 (61.1%), do not trust condom102 (46%) and I was drunken 87 (38%).…”
Section: Discussionmentioning
confidence: 94%
“…23,24 Regardless of the different strategies that promote condoms developed in this country, consistent condom use is still low in the police force. 25 The probable reason for this could be the information provided is not comprehensive enough and has not been tailored to this population as this is explained by this study. The main reasons for not using condoms consistently were reduced sexual pleasure 134 (61.1%), do not trust condom102 (46%) and I was drunken 87 (38%).…”
Section: Discussionmentioning
confidence: 94%
“…This is supported by a study conducted in Cameroon, which also revealed that the main reasons for inconsistent condom use included condom use-related stigma among Cameroonian soldiers. 37 According to a study conducted among Addis Ababa military and police personnel, the perception was the main reason for condom nonuse. 29 Lower condom use was associated with the perception that condoms make sex less enjoyable, as well as negative attitudes toward condoms, according to a study conducted among the Republic of Congo Defense Force.…”
Section: Discussionmentioning
confidence: 99%